Long-term outcomes and risk assessment of immediate implants at molar extraction sites in a Taiwan population - Shing-Zeng Dung; Jui Wang; Tzu-Hsuan Weng; Yu-Kang Tu (Scientific Reports)
Abstract This long-term retrospective study evaluated the clinical and radiographic outcomes and assessed the risks associated with immediate molar implants (IMI) in a Taiwan population. This study analyzed the clinical and radiographic records of 62 implants in 43 patients who received IMI and had follow-up periods of 2–16.5 years. After implantation, patients underwent radiographic and clinical assessments. The primary outcomes were implant survival rate, midfacial mucosal tissue recession (MTR) and peri-implant marginal bone loss (MBL), which were calculated at the implant level. Moreover, information on implant- and patient- related risk factors for peri-implantitis was recorded and analyzed by univariable and multivariate analyses through the generalized estimating equation method. Approximately half of the molar extraction sites exhibited unique root anatomy and were classified as type C socket. A significant association was observed between a history of periodontitis and three-rooted mandibular first molar and MBL. The implant survival rate was approximately 98%. A history of periodontitis, poor oral hygiene, keratinized mucosa (KM) < 2 mm, and a follow-up period of > 8 years significantly predicted higher MBL. Male patients and those with a history of periodontitis, poor oral hygiene, MTR, and follow-up period of > 8 years exhibited a significantly higher risk of peri-implantitis. This study confirms that the IMI is an effective and predictable treatment modality in a Taiwan population. The identified risk factors for peri-implantitis of IMI included a history of periodontitis, poor oral hygiene, KM < 2 mm, and a follow-up period of > 8 years.